Menyuntik Ushul Fiqh Dengan Filsafat - Iswahyudi Iswahyudi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to explore the integration of philosophy in ushul fiqh to enrich the methodological approach in understanding Islamic law. The philosophical approach is expected to provide a more rational and contextual perspective on the concepts in ushul fiqh. The method used is a literature study by analyzing classical and contemporary sources related to ushul fiqh and philosophy. The analysis was carried out descriptively and critically to identify the relevance of philosophical thought in the study of ushul fiqh. The results showed that a philosophical approach can deepen the understanding of the concepts of qiyas, maqashid shariah, and istihsan, as well as increase flexibility in the application of Islamic law in the modern era. This integration opens up space for a more adaptive renewal of Islamic law without losing its normative essence. Thus, philosophy can be an important instrument in developing a more dynamic and contextual ushul fiqh.